Questioning the Arabic Poetry Modernism in contemporary Arabic critical discourse : Hamid Samir as a Model - Amoura, Rachid; Bareche, Zahira (Journal of Human Sciences, 2023)
This research paper examines how modernity reached poetry among Arabs, and took the appellation of the Arabic poetry modernism. The research paper focuses particularly on the questioning that touched this modernity, with a particular emphasis on questioning by Doctor Samir Hadid as a model, to examine why and how the above-mentioned critic questioned Arabic poetry modernism.